1999
DOI: 10.1116/1.590576
|View full text |Cite
|
Sign up to set email alerts
|

Properties of gate quality silicon dioxide films deposited on Si–Ge using remote plasma-enhanced chemical vapor deposition with no preoxidation

Abstract: Articles you may be interested inComposition, structural, and electrical properties of fluorinated silicon-nitride thin films grown by remote plasmaenhanced chemical-vapor deposition from SiF 4 / NH 3 mixtures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In addition, the presence of a mixed oxide (SiO 2 ϩGeO 2 ) at the interface can induce a degradation of the electrical properties. 12 Thus we have intentionally limited the range of V b from 0 to Ϫ50 V. In order to improve the cleaning procedure, we have tested an in situ low pressure ͑5 mTorr͒ hydrogen plasma treatment prior to deposition for 5 min. 9 The oxide interface may be passivated by the use of hydrogen, so we performed the postoxidation annealing at a lower temperature ͑150°C͒ than in the case of silicon substrates.…”
Section: A Oxides Deposited On Simentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presence of a mixed oxide (SiO 2 ϩGeO 2 ) at the interface can induce a degradation of the electrical properties. 12 Thus we have intentionally limited the range of V b from 0 to Ϫ50 V. In order to improve the cleaning procedure, we have tested an in situ low pressure ͑5 mTorr͒ hydrogen plasma treatment prior to deposition for 5 min. 9 The oxide interface may be passivated by the use of hydrogen, so we performed the postoxidation annealing at a lower temperature ͑150°C͒ than in the case of silicon substrates.…”
Section: A Oxides Deposited On Simentioning
confidence: 99%
“…Plasmaenhanced chemical vapor deposition ͑PECVD͒ has also been used to deposit stoichiometric SiO 2 films at low temperature. 11,12 Tetraethylorthosilicate ͑TEOS͒, commonly employed in microelectronics for its very good conformality and SiO 2 -like film chemical composition, has been proposed a͒ Present address: CNR-IMETEM, Stradale Primosole 50, 95121 Catania, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…1 -3 It was shown that Ge pile-up at the interface during high-temperature oxidation results in bad interface quality 3,4 and recent results with low-temperature plasma oxidation and/or chemical vapour deposition (CVD) of oxide look promising to improve the electrical parameters. 5 Secondly, low energy oxygen bombardment of Si 1 x Ge x alloys opens a different approach for the formation of ultrathin oxide layers. 6,7 Another interesting topic is sputtering of Si 1 x Ge x with oxygen primary beams, which is important for dopant characterization of Si 1 x Ge x layers in modern device structures by secondary ion mass spectrometry (SIMS).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] When a strained Si 1Ϫx Ge x layer with Ge content (x Ͻ 0.5) is oxidized at high temperature (T Ͼ 700°C), due to the large difference between the heat of formation of SiO 2 and GeO 2 , SiO 2 is preferentially produced rather than GeO 2 . [11][12][13][14][15][16][17] However, those oxidation methods have shown additional problems, such as poor oxide quality and formation of parastic channel. Therefore, conventional thermal oxidation has been shown to result in undesired strain relaxation and formation of a Ge pileup layer below the oxide layer.…”
Section: Introductionmentioning
confidence: 99%